STUDI PENGELOLAAN KEUANGAN PADA ENTREPENEUR MUDA - Alifia, Pundi Rizqi Nur; Wulandari, Dewi Ayu (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
Financial management becomes interesting topic nowadays. There are many factors effects a person’s financial management behavior.  This research aims to analyze the influence of financial literacy, financial attitudes, the use of financial technology and income on the financial management of young entrepeneur in Surabaya. Data of this research is a primary data obtained from respondents. Data collection used a survey method by distributing online questionnaires to a students who hava a business. The sampling technique used is purposive sampling with a total of 186 respondents. SEM-PLS is used to analyze the collected data. The research results indicate that (1) Financial literacy, financial attitudes and the use of financial technology partially has a positive and significant effect on the financial management. (2) Income can not be a moderating variables between the influence of financial literacy on the financial management of students. These results have implications for the young entrepreneur to maintain their financial literacy, financial attitude and the use of financial technology to have a good financial management.